Second dose of measles-mumps-rubella-varicella vaccine (MMRV) and the risk of febrile convulsions. Issue 14 (25th March 2022) - Schäfer, Wiebke; Reinders, Tammo; Schink, Tania
Abstract: Introduction: Studies have shown an increased risk of febrile convulsions (FC) after first immunization with the quadrivalent measles-mumps-rubella-varicella vaccine (MMRV) compared to a first dose of measles-mumps-rubella vaccine (MMR) only or in combination with separately administered varicella vaccine (MMR + V). Therefore, it is recommended to give MMR + V at first dose and MMRV or MMR + V at second dose. Little is known on the risk of FC after MMRV at second dose, especially whether the risk depends on age, sex, history of FC or type of first dose vaccine. Methods: A retrospective cohort study using claims data from the German Pharmacoepidemiological Research database (GePaRD) was performed in children born between January 1st, 2004 and October 31st, 2015 who received two doses of MMRV, MMR + V or MMR. Cases were defined as hospitalization with a diagnosis of FC without neurological conditions coded as main discharge diagnosis. Unadjusted and adjusted odds ratios (OR) with 95% confidence intevals (CIs) were calculated to compare the risk of FC. Stratified analyses were performed to examine potential effect modification by age, sex, history of FC or type of first dose vaccine. Results: In the first 30 days after second dose vaccination, 464 FCs were observed in a cohort of 528, 639 children with a median age of 17 months. After adjustment for potential confounders, the adjusted OR for FC in the 30 days after vaccination was 1.25 (95% CI 0.67–2.30) for MMRV compared to MMR + V and 1.04 (0.82–1.32) for MMRV compared to MMR. History of FC was the most important risk factor with an OR of 36.26 (29.30–44.89). We found no effect modification by age, sex, history of FC, or type of first dose vaccine. Conclusion: Use of MMRV at second dose is not associated with an increased risk of FC compared to MMR + V or MMR, irrespective of age, sex, history of FC, or type of first dose vaccine.